Potentiality of Baycidal on the growth and development of malathion-sysceptible and multi-resistant strains of Tribolium castaneum (Herbst) treated at different larval ages (University Journal of Zoology, Rajshahi University, 2007)
Key words: Tribolium castaneum; growth, development, Larval ages, Baycidal Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp.37-39